Запорозький зимівник в останній чверті XVIII століття. (Zaporizhzhia Historical Review, 2021)
The article dwells upon the conditions and fate of cossacks’ farms-zymivnyks in the end of the XVIIIth century. It is shown, that by destroying cossacks’ farms the government had taken the guilt of turning Ukraine into the “wild plain” just to spend huge sums of money for inhabiting it later.